2022
DOI: 10.1371/journal.pone.0275492
|View full text |Cite
|
Sign up to set email alerts
|

Projecting Spanish fertility at regional level: A hierarchical Bayesian approach

Abstract: The transition from a demographic regime of high mortality and high fertility to one with low mortality and low fertility is universal and comes along with the process of socio-economic modernization. The Spanish total fertility rate has decreased to below replacement levels in the last decades. The decline has persisted since the 1960s and is diverse across the country. Based on that diversity, the use of population forecasts, not only at national but at regional levels, for planning purposes (governments and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
0
1
0
1
Order By: Relevance
“…На данный момент почти все международные организации при прогнозировании рождаемости используют именно байесовские иерархические модели. Этот методологический подход доказал свою эффективность на национальном уровне (Pelletier 2021), однако лишь относительно недавно стал применяться на региональном уровне к показателям рождаемости условных и реальных поколений (Rafael, García-Moreno, Pérez-Priego 2022).…”
Section: данные методы и первичное описание результатовunclassified
“…На данный момент почти все международные организации при прогнозировании рождаемости используют именно байесовские иерархические модели. Этот методологический подход доказал свою эффективность на национальном уровне (Pelletier 2021), однако лишь относительно недавно стал применяться на региональном уровне к показателям рождаемости условных и реальных поколений (Rafael, García-Moreno, Pérez-Priego 2022).…”
Section: данные методы и первичное описание результатовunclassified
“…Therefore, it randomizes over a realistic scenario space of future fertility patterns. Recently, Rafael Caro-Barrera et al [29] followed a similar approach with more detailed national data for stochastic TFR projections for all regions of Spain. In the case of Australia, Yang et al suggested a concept of including regional factors and migration backgrounds via means of the mother's birthplace into forecasts of ASFRs.…”
Section: Introduction 1background and Motivationmentioning
confidence: 99%